FRIENDS OF THE YUKON ARCHIVES SOCIETY, For the Record: Yukon Archives, 1972–2012 - Whyte, Douglas (Archivaria, 2013)
For the Record: Yukon Archives, 1972–2012. FRENDS OF THE YUKON ARCHIVES SOCIETY. Whitehorse, 2012. 74 p. ISBN 978-0-9879350-0-7.